Wreck : a novel - Newman, Catherine, 1968- (Harper, 2025)
"The acclaimed bestselling author of Sandwich is back with a wonderful novel, full of laughter and heart, about marriage, family, and what happens when life doesn't go as planned. If you loved Rocky and her family on vacation on Cape Cod, wait until you join them at home two years later. (And if this is your first meeting with this crew, get ready to laugh and cry-and relate.) Rocky, still anxious, nostalgic, and funny, is living in Western Massachusetts with her husband Nick and their daughter Willa, who's back home after college. Their son, Jamie, has taken a new job in New York, and Mort, Rocky's widowed father, has moved in. It all couldn't be more ridiculously normal . . . until Rocky finds herself obsessed with a local accident that only tangentially affects them-and with a medical condition that, she hopes, won't affect them at all. With her signature wit and wisdom, Catherine Newman explores the hidden rules of family, the heavy weight of uncertainty, and the gnarly fact that people-no matter how much you love them-are not always exactly who you want them to be"--